Contro l’esternalizzazione della pubblicazione e dell’insegnamento in ambito digitale - Paolo Monella (Lexicon Philosophicum)
Since schools and universities in Italy still have an instrumental, rather than a transformative, vision of information technology, they are outsourcing, as mere ‘services’, two key functions: scholarly publication and digital teaching. In the first case, the digital transition provides research institutions and funding agencies with a chance to ‘re-internalize’ publication. This would enhance both Open Access as well as innovative and open forms of communication and exchange in the academia (Open Data/Science). During the Covid-19 pandemic, schools and universities have been using platforms digital teaching belonging to the multinationals of digital mass profiling. Also, teaching and assessment techniques have rarely been renovated and adjusted to the new medium. As digital practices arisen during emergency distance learning become a permanent integration of blended education, schools and universities urgently need to tackle issues such as student and teacher personal data protection, constructivist digital learning methods and social inclusion policies.